First‐principles investigations on the synergistic effect of N‐dopant and lattice‐strain for CO2 reduction to CO on graphene. Issue 6 (7th November 2020) - Lu, Ruihu; Xia, Lixue; Wang, Huan; Zhao, Yan
Abstract: Improving the catalytic performance of graphene for the electrochemical CO2 reduction reaction (CO2 RR) has been a promising avenue to abate the concentration of greenhouse gas and develop a strategy of CO2 recyclable utilization. In this paper, we systematically investigate the catalytic performance of different active sites, both on the undoped and N‐doped graphene sheets, under non‐strained (0%) and 1%, 5% and 10% lattice strain (LS) via density functional theory calculations. The results uncover that N‐doping and LS synergistically modulate the electronic structures of graphene, enhancing the electrocatalytic reduction of CO2 to CO. Among all models in this work, the site with the highest catalytic activity toward CO2 RR is shown to be the carbon atom at the ortho ‐position (labeled as G2) relative to the nitrogen heteroatom (denoted by N1) on the graphene under 10% LS due to its lowest overpotential of 1.19 eV. Moreover, the projected density of states and the charge density differences of all systems are calculated to explore the mechanism for the enhancement of CO2 reduction performance. These analyses indicate that the localization of electron density on the G2 site makes it be the most active site on the N‐doped graphene sheet for CO2 RR. Hence, our computations demonstrate that by both nitrogen doping and LS increasing on the graphene sheet is a promising way for positive modulating its catalytic activity of the CO2 RR. Abstract : The synergistic effect of nitrogen doping and lattice strain increasing on graphene sheet was systematically investigated for CO2 reduction reaction via DFT calculations. The G2 site on the nitrogen‐doped graphene under 10% lattice strain was found to be the best active center for CO2 reduction to CO. Projected density of states and electron density difference analyses further revealed that the electron localization on the G2 site rendered the best activity.